2017
DOI: 10.4172/2572-0791.1000109
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Antidepressants, A Review of Significant Genetic Variants in Different Populations

Abstract: Major depressive disorder is a highly prevalent disease that is challenging to treat, often requiring medication and dose adjustments. Genetic factors play an important role in psychotropic medication responses. However, the translation of pharmacogenetics findings to clinical recommendations with regards to antidepressant responses is still in its early stages. We reviewed recent primary research articles, meta-analyses, and reviews on the pharmacogenetics of antidepressant treatment for major depressive diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…One subject with homozygote allele A/A for SNV rs1065852, associated with decreased CYP2D6 function, was found in our study sample, and we confirmed that the plasmatic t 1/2 increased about three times compared with A/G and G/G alleles. This SNV frequency in our study ( 1 / 24 = 4.2%) is consistent with reports in the literature, ranging from 2.8% and up to 4.3% in Caucasian, Hispanic, and Afro-American populations [ 37 ]. Together with CYP2D6 rs11358490, this SNV is part of the CYP2D6*10 haplotype [ 7 ], known to have decreased cytochrome function along with other gene variants [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…One subject with homozygote allele A/A for SNV rs1065852, associated with decreased CYP2D6 function, was found in our study sample, and we confirmed that the plasmatic t 1/2 increased about three times compared with A/G and G/G alleles. This SNV frequency in our study ( 1 / 24 = 4.2%) is consistent with reports in the literature, ranging from 2.8% and up to 4.3% in Caucasian, Hispanic, and Afro-American populations [ 37 ]. Together with CYP2D6 rs11358490, this SNV is part of the CYP2D6*10 haplotype [ 7 ], known to have decreased cytochrome function along with other gene variants [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Thus, pharmacogenetic test results would be more useful and accurate if laboratories sequenced the entire CYP2D6 gene, rather than selected polymorphisms. As a whole, sequencing would also provide a better depiction of the allelic variation within underrepresented communities (Barron et al, ; Bernard, ; Claudio‐Campos, Orengo‐Mercado, et al, ; Ortega & Meyers, ). Importantly, minority groups are predicted to become the majority by 2044, with a quarter being Hispanic (Colby & Ortman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Major depressive disorder is a mental health disorder characterized by persistently depressed mood or loss of interest in activities, causing significant impairment in daily life [ 122 ]. No pharmacogenomics studies in this context were extracted from Africa.…”
Section: Mental Disordersmentioning
confidence: 99%
“…However, a recent review highlighted eight genes implicated in antidepressant treatment response in mixed populations (including African-Americans). These included CYP2D6, CYP2C19, SLC6A4, ABCB1 (rs2032583 and rs2235015), FKBP5 (rs1360780, rs3800373 and rs4713916); GNB3 (rs5443); BDNF (rs6265); and HTR2A (rs7997012 and rs6313) [ 122 ]. Another study used genome-wide single nucleotide polymorphism data to examine independent contributions of race and genetic ancestry to antidepressant response [ 123 ].…”
Section: Mental Disordersmentioning
confidence: 99%